2015
DOI: 10.1128/jcm.02628-14
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Influenza C Viruses in the Philippines and Japan

Abstract: in the Philippines, 15 influenza C viruses were isolated, using MDCK cells, from specimens obtained from children with severe pneumonia and influenza-like illness (ILI). This is the first report of influenza C virus isolation in the Philippines. In addition, from January 2008 to December 2013, 7 influenza C viruses were isolated from specimens that were obtained from children with acute respiratory illness (ARI) in Sendai city, Japan. Antigenic analysis with monoclonal antibodies to the hemagglutinin-esterase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
6
21
0
Order By: Relevance
“…Here we described the isolation of a contemporary ICV—C/Victoria/2/2012 (C/Vic)—from a diseased child with acute respiratory symptoms in 2012. Phylogenetic analysis indicated that viral HEF gene was derived from C/Sao Paulo lineage, which is consistent with the finding that the dominant antigenic group is C/Sao Paulo lineage from 2006 to 2016 . However, its most internal genes (PB1, NP, M, and NS) were donated from multiple ICVs.…”
Section: Introductionsupporting
confidence: 86%
“…Here we described the isolation of a contemporary ICV—C/Victoria/2/2012 (C/Vic)—from a diseased child with acute respiratory symptoms in 2012. Phylogenetic analysis indicated that viral HEF gene was derived from C/Sao Paulo lineage, which is consistent with the finding that the dominant antigenic group is C/Sao Paulo lineage from 2006 to 2016 . However, its most internal genes (PB1, NP, M, and NS) were donated from multiple ICVs.…”
Section: Introductionsupporting
confidence: 86%
“…Therefore, C/Aichi/1/99 was circulating in Malaysia and had a genome composition distinct from that of C/Yamagata/1/93 (32). The increase in isolates belonging to the C/Sao Paulo lineage in Japan started in 2004 ( the Philippines in 2011 and 2013 had HE genes belonging to the C/Sao Paulo lineage and had the same internal genome composition as C/Miyagi/9/96 (43). Therefore, the viruses isolated in the Philippines are closely related to C/Victoria/2/2012, suggesting that such viruses of the C/Sao Paulo lineage were circulating in Australia and the Philippines in 2011 to 2013 before they spread to Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of influenza C viruses was performed using Madin–Darby canine kidney (MDCK) cells (ATCC CCL‐34) using maintenance media (DMEM Coon's Basal Media containing sodium bicarbonate (3%) with the addition of 2 mmol/L glutamine, 1% non‐essential amino acids, 0.05% NaHCO3, 0.02 mol/L HEPES, 4% penicillin and streptomycin, 2 μg/mL amphotericin B and 4 μg/mL trypsin). Samples were incubated for up to 5 days at 33°C without CO 2 , and virus growth was quantified by determining the hemagglutination titer (HA) with 0.5% fowl and turkey RBC …”
Section: Methodsmentioning
confidence: 99%
“…A Phylogenetic tree and the bootstrap supports for the HE data set were estimated using the best‐fit evolutionary model and the maximum likelihood (ML) method in PhyML, v3.0, software . Other representative influenza C viruses’ HE sequences were downloaded from GenBank, including the influenza C viruses that make up the antigenically and phylo‐genetically distinct reference groups: C/Taylor/1233.47, C/Aichi/1/81, C/Sao Paulo/378/82, C/Kanagawa/1/76, Yamagata/26/81 and C/Mississippi/80 . Bootstrapping estimates (%) were generated after running 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation